2021
DOI: 10.3389/fmars.2021.647943
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Coral Colony Surveys From In-Water Observations and Structure-From-Motion Imagery Shows Low Methodological Bias

Abstract: As the threats to coral reefs mount, scientists and managers are looking for innovative ways to increase the scope, scale, and efficiency of coral reef monitoring. Monitoring changes in coral communities and demographic features provides key information about ecosystem function and resilience of reefs. While most monitoring programs continue to rely on in-water visual survey methods, scientists are exploring 3D imaging technologies such as photogrammetry, also known as Structure-from-Motion (SfM), to enhance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…6), is lower than those reported from The standardization of underwater photogrammetry protocols needs to be considered. In a recent study, Couch et al (2021) detected no differences on the estimation of coral Relative coral cover range in the graphs is between 0 and 2.83. The colors represent each protocol.…”
Section: Coral Cover Colony Abundance and Species Richnessmentioning
confidence: 81%
See 2 more Smart Citations
“…6), is lower than those reported from The standardization of underwater photogrammetry protocols needs to be considered. In a recent study, Couch et al (2021) detected no differences on the estimation of coral Relative coral cover range in the graphs is between 0 and 2.83. The colors represent each protocol.…”
Section: Coral Cover Colony Abundance and Species Richnessmentioning
confidence: 81%
“…Urbina-Barreto et al (2021) showed that the LIT overestimates coral cover in comparison to UWP. However, Couch et al (2021) observed a high consistency of data between UWP and field visual surveys. Considering the advantages and recent integration of underwater photogrammetry to monitor coral reefs, there is a clear need to compare its performance with commonly used protocols.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Each sparse cloud was then scaled using image geospatial reference information, checked using the photogrammetric scale bars placed along the transect line and refined using between marker distances. Additionally, the total processing time is dependent on camera image resolution, the number of images being processed and computing power available for use (Bayley and Mogg, 2020;Couch et al, 2021).…”
Section: Photomosaic Assemblymentioning
confidence: 99%
“…These data are a valuable scientific resource, having been broadly used by NOAA, other United States federal agencies, State and Territorial partners, and key stakeholders for a variety of purposes. These include national stock assessments (e.g., Nadon, 2017Nadon, , 2019, endangered species reviews (e.g., Brainard et al, 2011), regional and multinational coral reef assessments (e.g., Brainard et al, 2008Brainard et al, , 2012Brainard et al, , 2019, and peer-reviewed papers geared toward the scientific community (e.g., Enochs et al, 2019;Allen et al, 2021;Couch et al, 2021). The data have also been used to produce technical documents and summary reports (e.g., Boyle et al, 2017;NOAA, 2018;McCoy et al, 2019) aimed at the coral reef management community and other coral reef stakeholder groups to inform resource management decision making, better tailor education and outreach programs at the jurisdiction level, and to evaluate the efficacy of existing programs aimed at reducing coral reef threats.…”
Section: Introductionmentioning
confidence: 99%